Periodontal and restorative integration for managing extreme gummy smiles with lip repositioning flap, crown lengthening, and lithium disilicate veneers: A case report - Daniyal Lazuardi Ramadhan; Galih Sampoerno; Widya Saraswati; Agung Krismariono; Tengku Natasha Eleena binti Tengku Ahmad Noor (Journal of Oral Biology and Craniofacial Research, 2025)
Background: Excessive gingival display, commonly referred to as a gummy smile, has a major impact on facial aesthetics and patient confidence. Addressing this condition often requires a multidisciplinary approach combining periodontal and restorative procedures. Purpose: This case report intends to demonstrate the efficacy of a comprehensive treatment strategy that included a lip repositioning flap, crown lengthening, and lithium disilicate veneers in achieving esthetic rehabilitation of an extreme gummy smile. Case: A 29-year-old male patient presented with excessive gingival display and short clinical crowns, resulting in a disharmonious smile. The patient expressed dissatisfaction with her smile aesthetics and sought a minimally invasive yet effective solution. Case management: The initial evaluation includes clinical and radiographic assessments to identify gingival biotype, crown-to-root ratio, and amount of gingival excess. A lip repositioning flap was performed to optimize gingival levels, followed by crown lengthening to expose adequate tooth structure for veneering. Lithium disilicate veneers were created utilizing a digital approach to improve precision and aesthetics. The treatment lasted six months, which ensured adequate healing and functional integration. Conclusion: The combination of periodontal surgery and advanced restorative techniques successfully addressed the patient's esthetic concerns, achieving a balanced gingival-dental relationship and a natural, harmonious smile. This case demonstrates the value of an interdisciplinary approach in managing complex esthetic challenges, providing predictable and satisfying outcomes for both clinicians and patients.